Real-Time Respiratory Monitoring Using a Sparse-Sampled Frequency-Scanning White-Light Interferometry System - Wenyan Liu; Cheng Qian; Kexin Li; Yiping Wang; Xiaoyan Cai; Qiang Liu (Photonics)
Fiber-optic tip sensors offer significant potential in biomedical applications due to their high sensitivity, compact size, and resistance to electromagnetic interference. This study focuses on advancing phase demodulation techniques for ultra-short Fabry–Pérot cavities within limited spectral bandwidths to enhance their application in biomedicine and diagnostics. We propose a novel sparse-sampled white-light interferometry system for respiratory monitoring, utilizing a monolithic integrated semiconductor tunable laser for quasi-continuous frequency scanning across 191.2–196.15 THz at a sampling rate of 5 kHz. A four-step phase-shifting algorithm (PSA) ensures precise phase demodulation, enabling high sensitivity for short-cavity fiber-optic sensors under constrained spectral bandwidth conditions. Humidity sensors fabricated via a self-growing polymerization process further enhance the system’s functionality. The experimental results demonstrate the system’s capability to accurately capture diverse breathing patterns—including normal, rapid, and deep states—with fast response and recovery times. These findings establish the system’s potential for real-time respiratory monitoring in clinical and point-of-care settings.